Snapshot of epigenetic regulation in legumes. Issue 3 (28th August 2020) - Windels, David; Dang, Thu Thi; Chen, Zhijuan; Verdier, Jerome
Abstract: In the current context of food security and increase in plant protein demand, legumes have an important role in facing challenges of climate change. With the recent improvement of sequencing technologies and the emergence of new knowledge related to plant epigenetic regulation in response to developmental and environmental changes, legume epigenetics is an emerging field with high potential for improving legume crop productivity and adaptability. The objective of this review is to provide a snapshot of epigenetic studies in different legume species. We have summarized the state‐of‐the‐art regarding legume epigenetic regulation controlling or participating in developmental aspects such as nodule, flower, and seed development and related to biotic and abiotic stresses. This extensive view of the different studies on legume epigenetics provides a baseline for identifying common and distinct mechanisms, and key players in epigenetic regulation from those of model species, such Arabidopsis, and highlights the impact that a better understanding of these mechanisms in legumes could have in order to improve plant productivity and adaptability. Abstract :